Evaluation of Nephrolithometric Scoring Systems to Predict Outcomes and Complications of Percutaneous Nephrolithotomy for Staghorn Stone - Yilmaz, Mehmet; Çil, Gökhan (Scripta Medica, 2023)
Background/Aim: Urinary system stone disease develops with a frequency of 1-20 % in the general population. There are various surgical methods and percutaneous nephrolithotomy (PCNL) is a commonly used treatment method, especially in large, staghorn kidney stones. Aim of this study was compare stone nomograms in forecasting operative and complicating parameters subsequent to PCNL in staghorn stones. Methods: The study analysed 66 patients with staghorn stones who underwent percutaneous nephrolithotomy between 2017 and 2022, retrospectively. The researcher evaluated the Guy, S.T.O.N.E. and CROSS nephrolithotomy scores in patients using non-contrast computed tomography. The Clavien Dindo Classification was used to evaluate the surgical complication. Results: The mean stone burden, GUY, S.T.O.N.E. and CROES scores were 1114.9 ± 52018 mm²; 3.64 ± 0.48; 10.11 ± 1.2 and 142.9 ± 31.99, respectively. Total stone-free status (SFS) was achieved in 37.9 % of the patients, while the median stone clearance rate was 93.74 (50-100). While no statistical significance was observed between GUY score and SFS, it was observed in S.T.O.N.E. and CROES scores (p = 0.020 and 0.004, respectively). ROC analysis showed that CROES and S.T.O.N.E. scoring systems and the stone burden parameter showed similar accuracy in the estimation of SFS. The results showed that only the S.T.O.N.E. score showed a significant relationship with the presence of complications (p = 0.034). Conclusion: If the percutaneous nephrolithotomy for staghorn stones in question is, current scoring systems alone couldn’t be predictive for postoperative outcomes and degree of complications. Further large scale multicentre prospective studies are needful.